A Best Practice of Book Inventory Project at a Medium-Sized Academic Library: How to Choose Hand-Held Inventory Devices and Handle Inventory Exceptions. Issue 1 (2nd January 2018) - Xu, Gordon F.
ABSTRACT: Recently, a book inventory project was conducted at a medium-sized academic library. Based on best practices, the author elaborates on the cost-effective inventory process, how to choose appropriate hand-held inventory devices, and how to handle inventory exceptions regarding a variety of related issues, including missing, mishelving, on-going shelf-reading, and varied inventory exceptions. Inventory could greatly reduce user frustration by providing more accurate information regarding the library collection for users. The author suggests useful recommendations based on the lessons learned from the project experience. The project experience presents in this article should be instructive for libraries undertaking similar inventory projects.